(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Recent high-intensity earthquakes have gained increasing media attention in a number of countries, including Nepal. Buildings’ structural insufficiency to handle seismic loads has been brought to light by the ensuing losses, mainly human life, caused by earthquakes. Post-earthquake studies have shown that masonry structures, in comparison to other building types, are the most earthquake-prone and have incurred the greatest damage during prior quakes . Even if many new building methods have been developed in the modern period, masonry still has a significant place in the construction business. As Nepal is highly under the sesmic forces no any codal provision is there before the 1992 A.D Earthquake. With the importance, Nepal introduced the code on 1994 A.D which on dealed mostly with the Sesmic Behaviour. After the Massive Earthquake on 2015A.D, there was the challenge on Upgrading the Codal Provision on NBC, which incorporated both the sesmic and dynamic forces, which results on NBC 105:2020. The primary purpose of the research is to examine multi-story reinforced concrete building models using static and dynamic analysis of the same design utilising the latest version of Nepal’s building code (NBC:105:2020). The Comparative study of the Static and Dynamic forces on G+9 Multistory RC Building is considered of the analysis.